The effectiveness of business partnership to the marketing of home industry products - Kamaludin Yusup, Deni (Opción, 2019)
The aim of this study is to analyze the effectiveness of business partnerships and co-branding on the marketing of home industry products in franchise companies. This study also uses a descriptive quantitative approach with a sample of 20 franchise companies. The results of the determination test showed 52.4%, while the remainder was 47.6%. Similarly, the beta coefficient test results on the business partnership variable are 0.364, while the co-branding variable is 0.289. In conclusion, business partnerships and co-branding partially and simultaneously have a positive and significant effect on the marketing of home industry products in franchise companies